The role of happiness in empathy self perception in medical and pharmacy students: A comparative study - Ana Catarina Andrade Nascimento (2020)
Introduction: The development of empathic skills during high school may be fostered by personal and contextual characteristics. The objective of this study was to explore the reciprocal relationship between happiness, academic satisfaction and empathy in university students attending healthcare degrees - pharmacy and medicine. We also aimed to clarify the role of happiness in self-perceived empathy in these two populations. Methods: A total of 364 pharmacy and 342 medical students of the first and second university years were included. Sociodemographic characteristics were assessed and a battery of questionnaires was used to evaluate empathy - Interpersonal Reactivity Index (IRI), academic satisfaction and subjective happiness - Subjective Happiness Scale (SHS). Results: Pharmacy students reported significantly higher IRI scores (p<0.001), and Academic Satisfaction (p=0.007) comparing with medical students. Nevertheless, these students presented higher scores in SHS than their pharmacy colleagues (p=0.05). A negative correlation was detected between SHS and empathy subscale personal discomfort in both students' groups. In the total sample significant positive correlations were detected between IRI-EC (p<0.001) and IRI-PT (p=0.002) and IRI-FS (p=0.015) subscales and Academic Satisfaction. Discussion: Distinct profiles were found in pharmacy and medical students in their self-perceived empathy, academic satisfaction, and subjective happiness. Sociodemographic characteristics contribute to partially explain these differences. Nevertheless, both groups of students showed a positive association between specific empathy dimensions and AS, and a negative association between personal discomfort and subjective wellbeing. Conclusions: Objective empathy assessment tailored for different healthcare setting may disentangle its relationship with subjective wellbeing and sociodemographic profile in health sciences university students. Present research confirms the role of academic satisfaction as a component of student's happiness.